Edukasi Terkait Permasalahan Stop Kontak Bertumpuk Di Rt 16 Dan Rt 27 Wonocatur, Banguntapan, Bantul - Musvita Ayu, Suci; Aqila, Syifa; Yasyukur Bakhiitah, Yukiko; Aulia Maarif, Fazri; Widayanti, Tri; Reynaldi, Royfanza; Dania Ramadhani, Shafa; Wardani, Yuniar (Universitas Pahlawan Tuanku Tambusai, 2023)
The goal of community diagnosis is to be able to find out how many people are exposed to diseases and problems in RT 16 & RT 27 so that in the future the community will not be exposed to these diseases and can find out how to prevent them properly and correctly. The problem solver uses the USG method and then the authors carry out MMD (Village Community Consultation) activities so that in the future the problem can get the right solution. Based on the results of the priority analysis that has been carried out, there are three problems, namely the storage of wet (organic) waste that is not separated, the use of stacked sockets, and hypertension. An alternative solution to the problem is carried out by conducting counseling using power point media and stickers. Prior to counseling as an alternative problem solving, MMD was carried out first to help solve existing problems in the community. Then by carrying out interventions with counseling it is hoped that the community can reduce the use of stacked sockets when using electronic equipment. Keywords: intervention, short circuit, fire, electricity